Brain neurons and glial cells express Neu differentiation factor/heregulin: a survival factor for astrocytes. - Pinkas-Kramarski, R (1994)
Neu differentiation factor (NDF, also called heregulin) was isolated from mesenchymal cells on the basis of its ability to elevate phosphorylation of ErbB proteins. Earlier in situ hybridization analysis showed that NDF was transcribed predominantly in the central nervous system during embryonic development. To gain insights into the role of NDF in brain we analyzed its distribution by immunohistochemistry and in situ hybridization. Late-gestation (day 17) rat embryos displayed high NDF immunoreactivity in both motor (e.g., putamen) and limbic (e.g., septum) regions. Lower levels of the factor were exhibited by adult brain, except for the cerebellum, where NDF expression was increased postnatally. Both neurons and glial cells were identified by immunohistochemistry as NDF-producing cells (e.g., pyramidal neurons in the cerebral cortex and glial cells in the corpus callosum). By establishment of primary cultures of rat brain cells we confirmed that NDF was expressed in neurons as well as in astrocytes. In addition, by using such primary cultures we observed that NDF treatment exerted only a limited mitogenic effect, which was accompanied by significant acceleration of astrocyte maturation. Furthermore, long-term incubation with the factor specifically protected astrocytes from apoptosis, implying that NDF functions in brain as a survival and maturation factor for astrocytes.